Growing China's renewables sector: a developmental state approach. Issue 6 (1st November 2016) - Chen, Geoffrey C.; Lees, Charles
ABSTRACT: Over the last decade China expanded its renewable energy sector with unprecedented speed. This success story presents a challenge to Western modes of environmental governance, where stakeholder participation is often deemed a necessary pre-condition for effective policy outcomes. Drawing on new research (including previously unpublished interview data), the article first discusses established modes of environmental governance before examining the growth of China's renewables sector through the theoretical lens of the 'developmental state'. The article then analyses renewable energy policy design and implementation in China, illustrating how top-down command and control strategies have successfully diffused renewable energy technology from a standing start. We argue that (1) China's distinct approach to the sector differs from Western modes of environmental governance and (2) this has revealed a new path towards renewable energy diffusion that authoritarian states in particular might regard as an attractive alternative to participatory models.